Development Of An Internship Model Using Outcome-Based Education (Obe) Curriculum - Agunawan, Agunawan; Muhammad Yahya; Ruslan, Ruslan (Cita konsultindo, 2025)
This study aims to develop an internship model based on the Outcome-Based Education (OBE) curriculum tailored to the needs of higher education institutions. The research adopts a Research and Development (R&D) approach using the INOBEL (Integrative Outcome-Based Education for Learning Outcomes) development model, which includes stages such as needs exploration, design, development, implementation, and evaluation. INOBEL was reconstructed from established models such as Borg and Gall, ADDIE, 4D, Dick and Carey, and DBR. The subjects involved in this study included students, academic supervisors, and industry partners. Data collection techniques included interviews, observations, documentation, and questionnaires, while data analysis was conducted both quantitatively and qualitatively. The results showed that the OBE-based internship model met the criteria of validity, practicality, and effectiveness in enhancing students' soft skills and hard skills. It also fostered collaboration between universities and industries, producing tangible outputs such as internship reports, scientific journals, or products eligible for intellectual property rights (HaKI). The study recommends disseminating the model among academic supervisors and implementing it more broadly within higher education institutions.